O sotaque alemão no "regionalismo" rio-grandense: história e práticas - Terhorst, Cristiele Aline Kuhn (2021)
The research addresses the history of the Centro de Tradições Gaúchas Estância do Imigrante in the municipality of Selbach, located in the middle plateau of Rio Grande do Sul. It was founded in the 1980s, late in comparison to the organization of regionalism in the Movimento Tradicionalista Gaúcho, which is investigated through bibliography and sources: minutes, interviews, websites, magazines, photographs and calendar of events. Through the study of the history of the MTG, the aim is to understand how the ideology of gauchismo was formed over the years and how it is constituted today. It uses the approach of oral history through the collection and analysis of interviews with founders of the traditionalist entity, using personal memory as an instrument for recording the facts that occurred in relation to the entity and that contributed to the construction of a collective identity. It analyzes the contradiction in the name of the CTG and the colonization of Selbach, which occurred with the arrival of descendants of Germans to occupy small plots of land with family farming, without any connection to the cattle ranching estate known in the state as estância. The aim is to understand how the association was established, what practices its members carried out and which continue to be carried out until 2021, so that it can be aligned with the MTG. It also aims to discuss the acculturation that occurred through the implementation of habits that were previously strange to the founders: the use of bombachas and prenda dresses, the use of horses as riding mounts, the reproduction of music considered to be gaucho in nature, the involvement with traditional dances in the establishment of adult and children's groups, and the subsequent organization of the Creole rodeo. It concludes that it was through the encouragement of people not born in the locality and the influence they exerted on the group invited to the first meeting that the CTG was created and an acculturation developed in the following years.